Mongolia : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The staff report for the 2010 Article IV Consultation underlies that in recent years, Mongolia's economy has performed quite well. The inflation pressures reflected a relaxation of monetary and fiscal policies and large increases in prices for food and fuel. The debt service burden and international reserves are expected to remain at comfortable levels. Executive Directors welcomed the authorities' purpose to review plans for the establishment of a development bank, taking account of the know-how elsewhere so as to avoid creating unfair competition in the financial sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet